Jordan : Second Review Under the Stand-By Arrangement, Request for Waivers of Nonobservance of Performance Criteria, and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses Jordan's Second Review Under the Stand-by Arrangement, Request for Waivers of Nonobservance of Performance Criteria (PCs), and Modification of PCs. Program performance is broadly on track. The central bank rebuilt reserves, which are now at a comfortable level and well above what was programmed. The national electricity company's losses were in line with the program through June, but the end-September PC is estimated to have been missed because a temporary interruption in gas flows required more expensive fuel imports. The IMF staff strongly supports the authorities' plans to seek higher grants.